Ethnic Differences in Elders' Home Remedy Use: Sociostructural Explanations - Grzywacz, Joseph G. (2006)
Objective: To determine if ethnic differences in elders' use of home remedies are explained by structured inequalities. Method: Dichotomous indicators of “food” and “other” home remedies were obtained from a randomly selected cohort of older adults with diabetes (N=701). Analyses evaluated if differences in availability of care, economic hardship, and health status explained ethnic differences in home remedy use. Results: Differences in residential location, discretionary money, and health partially explained greater home remedy use among Black and Native American elders relative to whites. Conclusions: Ethnic differences in elders' use of home remedies are not largely attributed to socially structured inequalities.